Identification of Student Learning Styles Using the Dempster-Shafer Theory Algorithm - Rizki Wahyudi; Noto Setyo Putro (Journal of Computer Science and Engineering (JCSE), 2020)
Abstract:In the school environment, learning is the interaction between educators and students that is done consciously, planned both inside and outside the room to improve the ability of students. But a person's ability to learn, understand and absorb lessons is different in level. Some are fast, moderate and some are very slow. Therefore, they often have to take different ways to understand the same information or lessons. This study aims to identify student learning styles by implementing the Dempster-Shafer Theory algorithm to help teachers determine the learning model that is suitable for each student. Students who were the object of this study were students of SMA N 1 Klampok Purwareja. The Dempster-Shafer Theory method can be used for the representation, combination and propagation of uncertainty, characteristics that are institutively following the way of thinking of an expert, this method can also distinguish the uncertainty and ignorance of the expert. So that research can be directed, the researcher uses the system development method ESDLC (Expert System Development Life Cycle) with stages of Assessment, Knowledge Acquisition, Design, Testing, Documentation, and Maintenance. The results of this study are student learning style learning applications that make it easy for teachers to determine learning models that are suitable for student.Abstrak: Di lingkungan sekolah, belajar adalah interaksi antara pendidik dengan peserta didik yang dilakukan secara sadar, terencana baik didalam maupun di luar ruangan untuk meningkatkan kemampuan peserta didik. Namun kemampuan seseorang dalam belajar, memahami dan menyerap pelajaran berbeda tingkatnya. Ada yang cepat, sedang dan ada pula yang sangat lambat. Karenanya, mereka seringkali harus menempuh cara berbeda untuk bisa memahami sebuah informasi atau pelajaran yang sama. Penelitian ini bertujuan untuk mengidentifikasi gaya belajar siswa dengan mengimplementasikan algoritma Dempster-Shafer Theory agar dapat membantu guru menentukan model pembelajaran yang cocok untuk masing-masing siswa. Siswa yang dijadikan objek penelitian ini adalah siswa SMA N 1 Klampok purwareja. Metode Dempster-Shafer Theory dapat digunakan untuk representasi, kombinasi dan propogasi ketidakpastian, karakteristik yang secara instutitif sesuai dengan cara berfikir seorang pakar, metode ini juga dapat membedakan ketidakpastian dan ketidaktahuan dari pakar. Agar penelitian dapat terarah maka peneliti menggunakan metode pengembangan sistem ESDLC (Expert System Development Life Cycle) dengan tahapan Assesment, Knowledge Acquisition, Design, Testing, Documentation, Dan Maintenance. Hasil penelitian ini sebuah aplikasi identifikasi gaya belajar siswa sehingga mempermudah guru untuk menentukan model pembelajaran yang cocok bagi siswa.